Fuel cell membrane electrode and method for producing the same, proton exchange membrane fuel cell
Patent Information
- Application Number
- CN202510440291.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-16
AI Technical Summary
[0008]本发明的目的是为了克服现有技术存在的膜电极传质效率差、电催化活性不理想的问题,提供一种燃料电池膜电极及其制备方法、质子交换膜燃料电池,该膜电极具有较高的电催化剂活性、传质效率高
[0016] By incorporating modified carbon particles into the catalyst layer, the hydrophilicity/hydrophobicity of the membrane electrode catalytic layer is altered. Furthermore, the interaction between the modified carbon particles and the catalyst facilitates the regulation of particle agglomerates within the catalyst layer, thereby controlling the porosity of both the anode and cathode catalyst layers. This constructs a unique three-phase reaction interface within the membrane electrode, enhancing its performance. The membrane electrode provided by this invention, while exhibiting electrocatalytic activity, achieves excellent oxygen diffusion and water transport, effectively reducing interfacial resistance and significantly improving membrane electrode performance.
Smart Images

Figure CN122930962A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fuel cell technology, specifically to a fuel cell membrane electrode and its preparation method, and a proton exchange membrane fuel cell. Background Technology
[0002] In recent years, the development of hydrogen energy technology has received increasing attention. Within the entire hydrogen energy industry chain, fuel cells are the core of hydrogen energy applications. Inside the membrane electrode assembly (MEA) of a fuel cell, the oxidation of hydrogen and the reduction of oxygen occur. The MEA is a multiphase coupled reaction process involving multiple reaction interfaces. The three-phase reaction interface is the region where the polymer, solid catalyst, and pore phase come into contact; it is the contact region for proton, electron, and gas transport channels, and is the only site where electrochemical reactions occur within the MEA. Therefore, the construction of the three-phase reaction interface inside the MEA is extremely critical, determining the final power and voltage output of the MEA.
[0003] Studies have shown that homogeneous catalyst layers prepared by traditional methods are not the ideal structure for optimal fuel cell performance. Therefore, optimizing the reaction interfaces within the membrane electrode assembly (MEA) is a major focus of current research. The traditional three-phase reaction interface is the contact region within the catalyst layer that connects the proton transport channels of the electrolyte, the gas transport channels of the flow field, and the electron transport channels between the Pt / C catalyst. Optimizing and designing the structures of the catalyst / support interface, the gas / liquid mass transfer interface, and the proton exchange membrane / catalyst layer / gas diffusion layer contact interfaces in the MEA is a crucial aspect of MEA design.
[0004] In existing membrane electrode designs, to enhance the hydrophilicity or hydrophobicity of the catalyst layer, hydrophobic substances (including polytetrafluoroethylene (PTFE) emulsion, polyvinylidene fluoride (PVDF) emulsion, or fluorocarbon resin) or hydrophilic substances (including polyvinyl alcohol) are often directly added to the slurry used to prepare the catalyst layer. However, in this case, the increase of the above-mentioned hydrophilic or hydrophobic substances will result in random distribution on the catalyst surface, which can easily lead to a large amount of coverage of the active sites of the catalytic reaction, resulting in a decrease in catalyst activity and a loss of utilization.
[0005] CN109921028A discloses a method that reduces the permeation of water from the anode side to the cathode side by setting hydrophobic Si films, polytetrafluoroethylene (PTFE) films, polyvinyl alcohol (PEO) films, etc., thereby mitigating the flooding phenomenon of the catalyst layer and gas diffusion layer on the cathode side, improving oxygen transport on the cathode side, reducing mass transfer polarization loss caused by oxygen transport, and improving the stability of the battery during long-term operation.
[0006] CN103531826A discloses a method for preparing a cathode and anode microporous layers by coating a carbon powder slurry containing MgO or ZnO nanomaterials onto a support layer, followed by coating a catalyst slurry containing MgO or ZnO nanomaterials onto the microporous layers to prepare cathode and anode catalyst layers. The prepared cathode and anode electrodes are then hot-pressed with a Nafion membrane to form a membrane electrode assembly (MEA). After thorough acid dissolution and washing, a nanoporous membrane electrode structure is obtained. This method modulates the three-phase reaction interface inside the membrane electrode by controlling the size of the oxide template, thereby altering the electrochemical performance and stability of the membrane electrode. However, a drawback is that the oxide is difficult to remove, and metal ions easily contaminate the membrane electrode.
[0007] Therefore, how to effectively regulate the mass transfer rate of the membrane electrode while maintaining its electrocatalytic activity is an important aspect of current membrane electrode research and development. Summary of the Invention
[0008] The purpose of this invention is to overcome the problems of poor mass transfer efficiency and unsatisfactory electrocatalytic activity of existing membrane electrodes, and to provide a fuel cell membrane electrode and its preparation method, as well as a proton exchange membrane fuel cell, which has high electrocatalytic activity and high mass transfer efficiency.
[0009] To achieve the above objectives, the present invention provides a fuel cell membrane electrode assembly, the membrane electrode assembly comprising a proton exchange membrane, wherein an anode catalyst layer is provided on one side of the proton exchange membrane and a cathode catalyst layer is provided on the other side;
[0010] The anode catalyst layer includes an anode catalyst and hydrophilically modified carbon particles, and the cathode catalyst layer includes a cathode catalyst and hydrophobically modified carbon particles.
[0011] The porosity of the anode catalyst layer is not less than 35%, and the contact angle between the anode catalyst layer and water is not higher than 95°; the porosity of the cathode catalyst layer is not less than 50%, and the contact angle between the cathode catalyst layer and water is not less than 90°, and the contact angle between the anode catalyst layer and water is smaller than the contact angle between the cathode catalyst layer and water.
[0012] A second aspect of the present invention provides a method for preparing the above-mentioned fuel cell membrane electrode, comprising:
[0013] (1) Prepare an anode catalyst layer slurry containing an anode catalyst, hydrophilically modified carbon particles, a dispersant and a solvent; prepare a cathode catalyst layer slurry containing a cathode catalyst, hydrophobically modified carbon particles, a dispersant and a solvent;
[0014] (2) Under heating conditions, the anode catalyst layer slurry is sprayed onto the surface of one side of the proton exchange membrane, and the cathode catalyst layer slurry is sprayed onto the surface of the other side of the proton exchange membrane.
[0015] A third aspect of the present invention provides a proton exchange membrane fuel cell, comprising the fuel cell membrane electrode described in the first aspect.
[0016] By incorporating modified carbon particles into the catalyst layer, the hydrophilicity / hydrophobicity of the membrane electrode catalytic layer is altered. Furthermore, the interaction between the modified carbon particles and the catalyst facilitates the regulation of particle agglomerates within the catalyst layer, thereby controlling the porosity of both the anode and cathode catalyst layers. This constructs a unique three-phase reaction interface within the membrane electrode, enhancing its performance. The membrane electrode provided by this invention, while exhibiting electrocatalytic activity, achieves excellent oxygen diffusion and water transport, effectively reducing interfacial resistance and significantly improving membrane electrode performance. Attached Figure Description
[0017] Figure 1 These are the power density curves of the membrane electrodes prepared in Example 1 and Comparative Example 1.
[0018] Figure 2 These are the polarization curves of the membrane electrodes prepared in Example 1 and Comparative Example 1. Detailed Implementation
[0019] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0020] The first aspect of the present invention provides a fuel cell membrane electrode, the membrane electrode comprising a proton exchange membrane, wherein an anode catalyst layer is provided on one side of the proton exchange membrane and a cathode catalyst layer is provided on the other side;
[0021] The anode catalyst layer includes an anode catalyst and hydrophilically modified carbon particles, and the cathode catalyst layer includes a cathode catalyst and hydrophobically modified carbon particles.
[0022] The porosity of the anode catalyst layer is not less than 35%, and the contact angle between the anode catalyst layer and water is not higher than 95°; the porosity of the cathode catalyst layer is not less than 50%, and the contact angle between the cathode catalyst layer and water is not less than 90°, and the contact angle between the anode catalyst layer and water is smaller than the contact angle between the cathode catalyst layer and water.
[0023] In existing membrane electrode designs, to adjust the hydrophilicity or hydrophobicity of the catalyst layer, hydrophobic substances (including polytetrafluoroethylene (PTFE) emulsions, polyvinylidene fluoride (PVDF) emulsions, or fluorocarbon resins) or hydrophilic substances (including polyvinyl alcohol) are often directly added to the slurry for preparing the catalyst layer. However, in this case, the increase of these hydrophilic or hydrophobic substances leads to their random distribution on the catalyst surface. Furthermore, substances directly added to the slurry may be directly adsorbed onto the catalyst surface, potentially covering the surface of the active metal of the catalyst. This results in extensive coverage of catalytic reaction active sites, affecting catalyst particle dispersion and causing a decrease in catalyst activity and utilization. The membrane electrode provided by this invention, by adding modified carbon powder particles to the catalyst layer, controls the appropriate porosity and hydrophilicity of the catalyst layer, enabling the construction of a special three-phase reaction interface within the membrane electrode and improving its performance. The membrane electrode provided by this invention, while maintaining electrocatalytic activity, achieves good oxygen diffusion and water transport and effectively reduces interfacial resistance, significantly improving the performance of the membrane electrode.
[0024] According to the present invention, the interaction between hydrophilically modified carbon particles and the anode catalyst is beneficial to adjusting the dispersion of particle agglomerates in the catalyst layer, thereby affecting the porosity of the catalyst layer. Preferably, the porosity of the anode catalyst layer is not less than 35%, and more preferably 40-55%. Controlling the porosity of the anode catalyst layer within the above-mentioned preferred range is beneficial to further improve the diffusion of oxygen and the transport performance of water, so that liquid water can be quickly discharged from the catalyst layer and the diffusion resistance can be reduced.
[0025] According to the present invention, the synergistic effect of the anode catalyst and the hydrophilically modified carbon particles gives the anode catalyst layer suitable hydrophilicity. The contact angle between the anode catalyst layer and water is no higher than 95°, preferably 60-80°, for example, specific contact angles such as 60, 65, 70, 75, 80°, or any range between the two. In the above-mentioned preferred case, it is beneficial to ensure that there is sufficient water in the catalyst layer to maintain the proton conduction rate, thereby further improving the performance of the membrane electrode.
[0026] The present invention allows for a wide range of choices regarding the thickness of the anode catalyst layer. Preferably, the thickness of the anode catalyst layer is 2-10 μm.
[0027] According to the present invention, the hydrophobically modified carbon particles facilitate the distribution of cathode catalyst particles in the catalyst layer. Preferably, the porosity of the cathode catalyst layer is not less than 50%, and more preferably 55-70%.
[0028] In this invention, the cathode catalyst layer has suitable hydrophobicity through the synergistic effect of the cathode catalyst and the hydrophobically modified carbon particles. The contact angle between the cathode catalyst layer and water is not less than 90°, preferably 100-110°, for example, it can be a contact angle of 100, 102, 105, 106, 110° or any range between the two.
[0029] According to the present invention, the contact angle between the anode catalyst layer and water is smaller than the contact angle between the cathode catalyst layer and water. Preferably, the contact angle between the anode catalyst layer and water is 10-50° smaller than the contact angle between the cathode catalyst layer and water, and more preferably 15-30°.
[0030] In this invention, by controlling the contact angles of the anode and cathode catalyst layers with water within the aforementioned preferred range, the anode and cathode catalyst layers possess suitable relative hydrophilicity and hydrophobicity, which is beneficial for further improving the electrochemical performance of the membrane electrode, especially exhibiting excellent performance in the high current density region.
[0031] The present invention allows for a wide range of choices regarding the thickness of the cathode catalyst layer. Preferably, the thickness of the cathode catalyst layer is 5-50 μm, and more preferably 5-25 μm.
[0032] In this invention, according to GB / T 19587-2017: Determination of Pore Size Distribution and Porosity of Porous Materials by Gas Adsorption Method, the porosity of the anode catalyst layer and the cathode catalyst layer is measured by the BET gas adsorption method.
[0033] In this invention, the contact angles between the anode catalyst layer and the cathode catalyst layer and water are measured by a static contact angle measurement method.
[0034] According to the present invention, the range of selection for the degree of hydrophilic modification of the hydrophilic modified carbon particles is relatively wide. Preferably, the oxygen content of the hydrophilic modified carbon particles is not less than 1 wt%, and more preferably 2-6 wt%.
[0035] In a preferred embodiment, the hydrophilic modified carbon particles and the anode catalyst particles are similar in size or smaller, which facilitates their guidance or more uniform distribution around the catalyst particles during the preparation of the membrane electrode slurry, thereby further enhancing the hydrophilicity of the catalyst particles. Preferably, the ratio of the average particle size of the anode catalyst to the average particle size of the hydrophilic modified carbon particles is 1:(0.8-1).
[0036] According to some preferred embodiments of the present invention, the average particle size of the hydrophilic modified carbon particles and / or hydrophobic modified carbon particles is 10-25 nm.
[0037] In this invention, the average particle size refers to the hydrodynamic radius of the particles in the solution, which is determined by dynamic light scattering (DLS) technology.
[0038] Preferably, in the anode catalyst layer, the mass ratio of the anode catalyst to the hydrophilic modified carbon particles is 1:(0.01-10), more preferably 1:(0.1-4). In the above preferred embodiment, it is advantageous for the anode catalyst layer to have suitable porosity and hydrophilicity.
[0039] The present invention does not impose any particular limitation on the modification method of the hydrophilic modified carbon particles, as long as the above-mentioned hydrophilicity requirements are met.
[0040] According to some preferred embodiments of the present invention, the method for preparing the hydrophilic modified carbon particles includes: contacting the carbon particles with a hydrophilic modifier, and then calcining them.
[0041] According to the present invention, the hydrophilic modifier can be selected from any conventional organic compound with hydrophilic groups in the art. Preferably, the hydrophilic modifier is selected from at least one of polyvinyl alcohol, cellulose, chitosan, and carbomer, and more preferably polyvinyl alcohol. The above-mentioned hydrophilic modifier can disperse and adsorb onto carbon particles during contact, and calcination can increase the oxygen content on the surface of the carbon powder, thereby improving hydrophilicity.
[0042] Preferably, the contact is carried out under ultrasonic and / or stirring conditions. The present invention does not have particular limitations on the ultrasonic or stirring conditions, as long as the carbon particles and the hydrophilic modifier can be uniformly dispersed.
[0043] According to the present invention, the range of selection for the amount of the hydrophilic modifier is relatively wide, as long as the oxygen content of the hydrophilic modified carbon particles is within the above-mentioned preferred range. Preferably, the mass ratio of the hydrophilic modifier to the carbon particles is 1:(3-10), more preferably 1:(4-8).
[0044] Preferably, the preparation method further includes drying the product after contact. The drying can be carried out using methods and conditions conventional in the art, and the present invention does not impose any particular limitations on this.
[0045] According to the present invention, preferably, the calcination temperature is 250-350°C and the time is 20-60 min.
[0046] According to the present invention, the oxygen content of the hydrophobically modified carbon particles is less than 0.5 wt%.
[0047] In this invention, the carbon particles can be commercially available, for example, at least one of conductive carbon black Vulcan XC72, Vulcan XC800 and Blackpearls 3000.
[0048] In a preferred embodiment, the hydrophobically modified carbon particles and the cathode catalyst particles are similar in size or smaller, which facilitates their guidance or more uniform distribution around the catalyst particles during the preparation of the membrane electrode slurry, thereby further enhancing the hydrophobicity of the catalyst particles. Preferably, the ratio of the average particle size of the cathode catalyst to the average particle size of the hydrophobically modified carbon particles is 1:(1-2).
[0049] Preferably, in the cathode catalyst layer, the mass ratio of the cathode catalyst to the hydrophobically modified carbon particles is 1:(0.1-10), more preferably 1:(0.25-4).
[0050] According to some preferred embodiments of the present invention, the method for preparing the hydrophobically modified carbon particles includes: contacting the carbon particles with a hydrophobic modifier, and then calcining them.
[0051] According to the present invention, the hydrophobic modifier may be selected from any conventional organic compound with hydrophobic groups in the art. Preferably, the hydrophobic modifier is selected from at least one of polytetrafluoroethylene, silane-modified materials, fluorocarbon resins, polymethyl methacrylate, and polypropylene, and is preferably polytetrafluoroethylene.
[0052] According to the present invention, preferably, the mass ratio of the hydrophobic modifier to the carbon particles is 1:(3-10), more preferably 1:(2-6).
[0053] Preferably, the preparation method further includes drying the product after contact. The drying can be carried out using methods and conditions conventional in the art, and the present invention does not impose any particular limitations on this.
[0054] Preferably, the roasting temperature is 250-350℃ and the time is 20-60 minutes.
[0055] According to some preferred embodiments of the present invention, the anode catalyst layer and the cathode catalyst layer each independently comprise an ionomer selected from perfluorosulfonic acid polymers, such as Nafion series perfluorosulfonic acid polymers (produced by DuPont). The ionomers in the anode catalyst layer and the cathode catalyst layer may be the same or different.
[0056] According to the present invention, preferably, in the membrane electrode, an anode diffusion layer is provided on the surface of the anode catalyst layer and a cathode diffusion layer is provided on the surface of the cathode catalyst layer along the proton exchange membrane outward.
[0057] The present invention offers a wide range of choices for the specific types of the anode diffusion layer and the cathode diffusion layer.
[0058] According to the present invention, preferably, the anode gas diffusion layer and the cathode gas diffusion layer may be the same or different, and each may be independently selected from carbon paper and / or microporous layers, for example, any one of the 28BC series diffusion layers from JNTG of South Korea or SGL of Germany.
[0059] In this invention, there are no particular requirements regarding the types of the anode and cathode catalysts; any conventional catalyst system in the art can be used, and the anode and cathode catalysts can be the same or different. Preferably, the anode and cathode catalysts are each independently selected from Pt / C catalysts and / or Pt / X catalysts, wherein X is selected from at least one of Co, Ni, Mo, Pd, and Au.
[0060] This invention offers a wide range of material options for the proton exchange membrane, allowing the use of any conventional proton exchange membrane suitable for fuel cell membrane electrodes. Preferably, the proton exchange membrane is a perfluorosulfonic acid polymer membrane.
[0061] A second aspect of the present invention provides a method for preparing the above-mentioned fuel cell membrane electrode, comprising:
[0062] (1) Prepare an anode catalyst layer slurry containing an anode catalyst, hydrophilically modified carbon particles, a dispersant and a solvent; prepare a cathode catalyst layer slurry containing a cathode catalyst, hydrophobically modified carbon particles, a dispersant and a solvent;
[0063] (2) Under heating conditions, the anode catalyst layer slurry is sprayed onto the surface of one side of the proton exchange membrane, and the cathode catalyst layer slurry is sprayed onto the surface of the other side of the proton exchange membrane.
[0064] According to some preferred embodiments of the present invention, in the anode catalyst slurry, the mass ratio of anode catalyst, solvent and dispersant is 1:(20-100):(100-800), preferably 1:(60-90):(200-650).
[0065] In this invention, the definitions of the anode catalyst and the hydrophilic modified carbon particles are the same as in the first aspect, and will not be repeated here.
[0066] In this invention, the dispersant can be selected from any substance in the art capable of improving the dispersibility of the components in the slurry. Preferably, the dispersant is an alcohol compound, preferably at least one selected from isopropanol, butyl acetate, ethylene glycol, and n-butanol.
[0067] In this invention, the solvent is preferably water.
[0068] According to the present invention, preferably, the mass ratio of cathode catalyst, solvent and dispersant in the cathode catalyst slurry is 1:(20-100):(100-800), more preferably 1:(40-80):(200-400).
[0069] In this invention, the range of solvents and dispersants in the cathode catalyst layer slurry is the same as that in the anode catalyst layer slurry. The specific types may be the same or different, and those skilled in the art can choose according to actual needs.
[0070] According to the present invention, preferably, the anode catalyst layer slurry and the cathode catalyst layer slurry each independently include an ionomer. The definition of the ionomer is the same as in the first aspect and will not be repeated here. The ionomer can be provided by an aqueous solution of the ionomer, preferably with a concentration of 2-30 wt%.
[0071] Preferably, the mass ratio of the anode catalyst or cathode catalyst to the ion polymer is (0.1-10):1, more preferably (1-5):1, for example, it can be a specific mass ratio such as 1:1, 2:1, 3:1, 4:1, 5:1 or any range between the two.
[0072] In this invention, the spraying can be carried out using conventional operating methods and conditions in the art, as long as the slurry can be evenly covered on the surface of the proton exchange membrane.
[0073] Preferably, in step (2), the heating conditions are 60-80℃, for example, 60, 65, 70, 75, 80℃, etc.
[0074] According to some preferred embodiments of the present invention, the preparation method further includes: covering the surface of the anode catalyst layer with an anode diffusion layer, covering the surface of the cathode catalyst layer with a cathode diffusion layer, and then performing hot pressing.
[0075] The anodic diffusion layer and the cathode diffusion layer are defined in the same way as in the first aspect.
[0076] Preferably, the hot pressing conditions include: a temperature of 100-140℃, more preferably 120-138℃; and a pressure of 2-8 kg / cm². 2 The preferred value is 4-7 kg / cm². 2 The pressure holding time is 100-200s, preferably 120-200s.
[0077] The present invention further provides a method for preparing a membrane electrode, comprising:
[0078] S1. The carbon particles are contacted with a hydrophilic modifier and then calcined to obtain hydrophilic modified carbon particles; preferably, the hydrophilic modifier is selected from at least one of polyvinyl alcohol, cellulose, chitosan and carbomer.
[0079] S2. The carbon particles are brought into contact with a hydrophobic modifier and then calcined to obtain hydrophobically modified carbon particles; preferably, the hydrophobic modifier is selected from polytetrafluoroethylene.
[0080] S3. Prepare an anode catalyst slurry containing an anode catalyst, hydrophilically modified carbon particles, a dispersant, and a solvent; prepare a cathode catalyst slurry containing a cathode catalyst, hydrophobically modified carbon particles, a dispersant, and a solvent.
[0081] S4. Under heating conditions, the anode catalyst layer slurry is sprayed onto the surface of one side of the proton exchange membrane, and the cathode catalyst layer slurry is sprayed onto the surface of the other side of the proton exchange membrane.
[0082] S5. Cover the surface of the anode catalyst layer with an anode diffusion layer and the surface of the cathode catalyst layer with a cathode diffusion layer, and then perform hot pressing.
[0083] A third aspect of the present invention provides a proton exchange membrane fuel cell, comprising the fuel cell membrane electrode described in the first aspect.
[0084] The present invention does not particularly limit other components of the proton exchange membrane fuel cell, as long as they include the above-mentioned fuel cell membrane electrode.
[0085] The present invention will be described in detail below through embodiments.
[0086] Example 1
[0087] (1) 10 mg of Blackpearls 3000 carbon powder particles (average particle size of 12-20 nm) were thoroughly mixed with 10 mg of 20% polyvinyl alcohol (PVA) solution, ultrasonically dispersed, dried, and then calcined at 300 °C for 30 min to prepare hydrophilic modified carbon particles, denoted as PVA@Blackpearls3000. The oxygen content in PVA@Blackpearls 3000 was determined to be 6 wt% by XPS method.
[0088] 10 mg of Blackpearls 3000 carbon powder particles were thoroughly mixed with 10 mg of 20% polytetrafluoroethylene (PTFE) solution, ultrasonically dispersed, dried, and then calcined at 300℃ for 30 min to prepare hydrophobically modified carbon particles, denoted as PTFE@Blackpearls 3000. The oxygen content in PTFE@Blackpearls 3000 was determined to be 0.4 wt% by XPS method.
[0089] (2) 8 mg of Pt / C catalyst (70 wt.% Pt loading, average particle size of catalyst 12-20 nm) and 10 mg of PTFE@Blackpearls 3000 were placed in a glass bottle, followed by the addition of 345 mg of water and ultrasonic vibration several times. Then, 98 mg of Nafion solution (5 wt.%) was added, followed by vibration several times. Finally, 1885 mg of isopropanol was added, and ultrasonic vibration was performed for 30 min to obtain the cathode catalyst slurry. The mass ratio of cathode catalyst, water, and isopropanol was 1:43:236. The surface temperature of the substrate containing the proton exchange membrane (Nafion 211) was controlled at 70 °C. The cathode catalyst slurry was sprayed onto the proton exchange membrane using a sprayer to prepare the cathode catalyst layer. The cathode catalyst layer had a thickness of 24 μm, a porosity of 56%, a contact angle between the cathode catalyst layer and water of 105°, and a catalyst loading of 1 mg / cm³. 2 .
[0090] (3) 4 mg of Pt / C (70 wt.%) catalyst and 1 mg of PVA@Blackpearls 3000 were placed in a glass bottle, followed by the addition of 345 mg of water and ultrasonic vibration several times. Then, 49 mg of Nafion solution (5 wt.%) was added, followed by vibration several times. Finally, 1885 mg of isopropanol was added, and ultrasonic vibration was performed for 30 min to obtain the anode catalyst layer slurry. The surface temperature of the substrate containing the proton exchange membrane (Nafion 211) was controlled at 70 °C, and the anode catalyst layer was prepared by spraying the anode catalyst layer slurry onto the proton exchange membrane using a sprayer. The thickness of the anode catalyst layer was 10 μm, the porosity was 43%, the contact angle between the anode catalyst layer and water was 78°, and the catalyst loading was 0.2 mg / cm³. 2 .
[0091] (4) The cathode diffusion layer (SGL28BC) and the anode diffusion layer are covered on the outer surface of the above-mentioned catalyst layer, and hot-pressed at a temperature of 120°C and a pressure of 4 kg / cm². 2 The time was 200s, and the membrane electrode was obtained.
[0092] Example 2
[0093] (1) 10 mg of Blackpearls 3000 carbon powder particles (average particle size of 12-20 nm) were thoroughly mixed with 10 mg of 20% polyvinyl alcohol (PVA) solution, ultrasonically dispersed, dried, and then calcined at 300 °C for 30 min to prepare hydrophilic modified carbon particles, denoted as PVA@Blackpearls3000. The oxygen content in PVA@Blackpearls 3000 was determined to be 6 wt% by XPS method.
[0094] 10 mg of Blackpearls 3000 carbon powder particles were thoroughly mixed with 10 mg of 20% polytetrafluoroethylene (PTFE) solution, ultrasonically dispersed, dried, and then calcined at 300℃ for 30 min to prepare hydrophobically modified carbon particles, denoted as PTFE@Blackpearls 3000. The oxygen content in PTFE@Blackpearls 3000 was determined to be 0.4 wt% by XPS method.
[0095] (2) 8 mg of Pt / C catalyst (70 wt.% Pt loading, average particle size of catalyst 12-20 nm) and 2 mg of PTFE@Blackpearls 3000 were placed in a glass bottle, followed by the addition of 345 mg of water and ultrasonic vibration several times. Then, 98 mg of Nafion solution (5 wt.%) was added, followed by vibration several times. Finally, 1885 mg of isopropanol was added, and ultrasonic vibration was performed for 30 min to obtain the cathode catalyst slurry. The surface temperature of the substrate containing the proton exchange membrane (Nafion 211) was controlled at 70 °C, and the cathode catalyst slurry was sprayed onto the proton exchange membrane using a sprayer to prepare the cathode catalyst layer. The cathode catalyst layer had a thickness of 16 μm, a porosity of 55%, a contact angle between the cathode catalyst layer and water of 95°, and a catalyst loading of 1 mg / cm³. 2 .
[0096] (3) 4 mg of Pt / C (70 wt.%) catalyst and 4 mg of PVA@Blackpearls 3000 were placed in a glass bottle, followed by the addition of 345 mg of water and ultrasonic vibration several times. Then, 49 mg of Nafion solution (5 wt.%) was added, followed by vibration several times. Finally, 1885 mg of isopropanol was added, and ultrasonic vibration was performed for 30 min to obtain the anode catalyst slurry. The surface temperature of the substrate containing the proton exchange membrane (Nafion 211) was controlled at 70 °C, and the anode catalyst layer was prepared by spraying the anode catalyst slurry onto the proton exchange membrane using a sprayer. The thickness of the anode catalyst layer was 12 μm, the porosity was 44%, the contact angle between the anode catalyst layer and water was 75°, and the catalyst loading was 0.2 mg / cm³. 2 .
[0097] (4) The cathode diffusion layer (SGL28BC) and the anode diffusion layer are covered on the outer surface of the above-mentioned catalyst layer, and hot-pressed at a temperature of 120°C and a pressure of 4 kg / cm². 2 The time was 200s, and the membrane electrode was obtained.
[0098] Example 3
[0099] The method is the same as in Example 1, except that in step (2), the amount of PTFE@Blackpearls 3000 added is 50 mg, the porosity of the cathode catalyst layer is 50%, and the contact angle between the cathode catalyst layer and water is 125°.
[0100] Example 4
[0101] The method is the same as in Example 1, except that in step (3), the amount of PVA@Blackpearls 3000 added is 20 mg, the porosity of the anode catalyst layer is 35%, and the contact angle between the anode catalyst layer and water is 55°.
[0102] Example 5
[0103] The method is the same as in Example 1, except that the carbon particles used in step (1) are carbon materials purchased from Cabot, with an average particle size of 42 nm.
[0104] The porosity of the anode catalyst layer is 48%, and the contact angle between the anode catalyst layer and water is 57°.
[0105] The porosity of the cathode catalyst layer is 61%, and the contact angle between the cathode catalyst layer and water is 98°.
[0106] Comparative Example 1
[0107] (2) 8 mg of Pt / C catalyst (70 wt.% Pt loading, average particle size of catalyst 12-20 nm) and 10 mg of unmodified Blackpearls 3000 carbon particles were placed in a glass bottle, and then 345 mg of water was added. The mixture was ultrasonically vibrated several times. Then 98 mg of Nafion solution (5 wt.%) was added, and the mixture was vibrated several times. Finally, 1885 mg of isopropanol was added, and the mixture was ultrasonically vibrated for 30 min to obtain the cathode catalyst slurry. The surface temperature of the substrate on which the proton exchange membrane (Nafion 211) was located was controlled at 70 °C. The cathode catalyst slurry was sprayed onto the proton exchange membrane using a sprayer to prepare the cathode catalyst layer. The thickness of the cathode catalyst layer was 20 μm, the porosity was 33%, and the contact angle between the cathode catalyst layer and water was 90°.
[0108] (3) 4 mg of Pt / C (70 wt.%) catalyst and 1 mg of unmodified carbon particles (Blackpearls 3000) were placed in a glass bottle, and then 345 mg of water was added. The mixture was ultrasonically vibrated several times. Then, 49 mg of Nafion solution (5 wt.%) was added, and the mixture was vibrated several times. Finally, 1885 mg of isopropanol was added, and the mixture was ultrasonically vibrated for 30 min to obtain the anode catalyst slurry. The surface temperature of the substrate on which the proton exchange membrane (Nafion 211) was located was controlled at 70 °C. The anode catalyst layer was prepared by spraying the anode catalyst slurry onto the proton exchange membrane using a sprayer. The thickness of the anode catalyst layer was 8 μm, the porosity was 32%, and the contact angle between the anode catalyst layer and water was 91°.
[0109] (4) The cathode diffusion layer (SGL28BC) and the anode diffusion layer are covered on the outer surface of the above-mentioned catalyst layer, and hot-pressed at a temperature of 120°C and a pressure of 4 kg / cm². 2 The time was 200s, and the membrane electrode was obtained.
[0110] Comparative Example 2
[0111] (1) 8 mg of Pt / C (70 wt.%) catalyst and 5 mg of Blackpearls 3000 were placed in a glass bottle, followed by the addition of 345 mg of water and ultrasonic vibration several times. Then, 98 mg of Nafion solution (5 wt.%) was added, followed by vibration several times. Then, 5 mg of 20% polytetrafluoroethylene (PTFE solution) was added, and finally, 1885 mg of isopropanol was added. The mixture was ultrasonically vibrated for 30 min to obtain the cathode catalyst slurry. The surface temperature of the substrate on which the proton exchange membrane (Nafion 211) was located was controlled at 70 °C. The cathode catalyst slurry was sprayed onto the proton exchange membrane using a sprayer to prepare the cathode catalyst layer. The cathode catalyst layer had a thickness of 19 μm, a porosity of 46%, and a contact angle of 82° between the cathode catalyst layer and water.
[0112] (2) 4 mg of Pt / C (70 wt.%) catalyst and 0.5 mg of Blackpearls 3000 were placed in a glass bottle, followed by 345 μL of water and ultrasonic vibration several times. Then, 53 μL of Nafion solution (5 wt.%) was added, followed by vibration several times. Then, 0.5 mg of 20% polyvinyl alcohol solution was added, and finally 2400 μL of isopropanol was added. The mixture was ultrasonically vibrated for 30 min to obtain the anode catalyst slurry. The surface temperature of the substrate containing the proton exchange membrane (Nafion211) was controlled at 70 °C. The anode catalyst layer was prepared by spraying the anode catalyst slurry onto the proton exchange membrane using a sprayer. The thickness of the anode catalyst layer was 8 μm, the porosity was 34%, and the contact angle between the anode catalyst layer and water was 88°.
[0113] (3) The cathode diffusion layer (SGL28BC) and the anode diffusion layer are covered on the outer surface of the above-mentioned catalyst layer, and hot-pressed at a temperature of 120°C and a pressure of 4 kg / cm². 2 The time was 200s, and the membrane electrode was obtained.
[0114] Test case
[0115] Place two bipolar plates (from Qunyi Company, made of graphite, with a serpentine channel and a flow channel size of 5×5cm) on a flat table. Then place a piece of polytetrafluoroethylene paper with a square hole in the middle on the bipolar plates. Place two copper plates on both sides of the two bipolar plates to collect current. At the same time, there are heating pads on both sides of the clamping plate. Place the membrane electrode in the middle of the bipolar plates and fix it.
[0116] The single-cell test instrument is the Scribner 850e test system, with a maximum test current of 50A. The gases at the anode and cathode are oxygen and hydrogen, respectively, with a flow rate of 800mL / min, a back pressure of 2atm, and a temperature of 80℃.
[0117] The power density and polarization curves of the membrane electrode assemblies (MEAs) of each embodiment were tested, and the limiting current density (i.e., the current density when the voltage is 0) was calculated based on the polarization curve equation of the fuel cell. The power density curves of the MEAs prepared in Example 1 and Comparative Example 1 are shown below. Figure 1 As shown, the polarization curve is as follows Figure 2 As shown.
[0118] The limiting current density and peak power density of the membrane electrodes prepared in the above embodiments and comparative examples are shown in Table 1.
[0119] Table 1
[0120]
[0121]
[0122] from Figure 1 and Figure 2 The results show that the membrane electrode provided by this invention has better electrochemical performance. The membrane electrode of Example 1 exhibits better electrochemical performance at a current of 6299 mA / cm². 2 At this point, the power density reaches its peak value of 2795.9 mW / cm³. 2 Comparative Example 1: The membrane electrode at 5698.5 mA / cm 2 At that location, it reached a peak of 2314.2 mW / cm². 2 Meanwhile, the optimized membrane electrode achieves 3699.3 mA / cm² at 0.60 V. 2 The current density can reach 2899.7 mA / cm² at 0.60 V for conventional membrane electrodes. 2The current density.
[0123] The results of the limiting current density calculations in Table 1 show that, at high current densities, the oxygen transport resistance inside the membrane electrode prepared in this embodiment of the invention is reduced, the limiting current density is increased, and the mass transfer effect between liquid water and gas is enhanced, thus making the membrane electrode performance superior to that of conventional membrane electrodes. Furthermore, the polarization curves indicate that the kinetic polarization and concentration polarization of the membrane electrode prepared in this embodiment of the invention are reduced, while the increase in limiting current density demonstrates the enhanced mass transfer effect between liquid water and gas.
[0124] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A fuel cell membrane electrode assembly, characterized in that, The membrane electrode includes a proton exchange membrane, with an anode catalytic layer on one side and a cathode catalytic layer on the other side. The anode catalyst layer includes an anode catalyst and hydrophilically modified carbon particles, and the cathode catalyst layer includes a cathode catalyst and hydrophobically modified carbon particles. The porosity of the anode catalyst layer is not less than 35%, and the contact angle between the anode catalyst layer and water is not higher than 95°; the porosity of the cathode catalyst layer is not less than 50%, and the contact angle between the cathode catalyst layer and water is not less than 90°, and the contact angle between the anode catalyst layer and water is smaller than the contact angle between the cathode catalyst layer and water.
2. The fuel cell membrane electrode according to claim 1, wherein, The porosity of the anode catalyst layer is 40-55%; Preferably, the contact angle between the anode catalyst layer and water is 60-80°; Preferably, the thickness of the anode catalyst layer is 2-10 μm; Preferably, the porosity of the cathode catalyst layer is 55-70%; Preferably, the contact angle between the cathode catalyst layer and water is 100-110°; Preferably, the thickness of the cathode catalyst layer is 5-50 μm; Preferably, the contact angle between the anode catalyst layer and water is 10-50° smaller than that between the cathode catalyst layer and water, and more preferably 15-30°.
3. The fuel cell membrane electrode according to claim 1 or 2, wherein, The oxygen content of the hydrophilic modified carbon particles is not less than 1 wt%, preferably 2-6 wt%; Preferably, the ratio of the average particle size of the anode catalyst to the average particle size of the hydrophilically modified carbon particles is 1:(0.8-1); Preferably, in the anode catalyst layer, the mass ratio of the anode catalyst to the hydrophilically modified carbon particles is 1:(0.01-10), more preferably 1:(0.1-4); Preferably, the loading of the anode catalyst in the anode catalyst layer is 0.1-0.8 mg / cm³. 2 .
4. The fuel cell membrane electrode according to any one of claims 1-3, wherein, The method for preparing the hydrophilic modified carbon particles includes: The carbon particles are brought into contact with a hydrophilic modifier and then calcined. Preferably, the hydrophilic modifier is selected from at least one of polyvinyl alcohol, cellulose, chitosan, and carbomer; Preferably, the mass ratio of the hydrophilic modifier to the carbon particles is 1:(3-10); Preferably, the roasting temperature is 250-350℃ and the time is 20-60 minutes.
5. The fuel cell membrane electrode assembly according to any one of claims 1-4, wherein, The oxygen content of the hydrophobically modified carbon particles is less than 0.5 wt%. Preferably, the ratio of the average particle size of the cathode catalyst to the average particle size of the hydrophobically modified carbon particles is 1:(1-2); Preferably, in the cathode catalyst layer, the mass ratio of the cathode catalyst to the hydrophobically modified carbon particles is 1:(0.1-10), more preferably 1:(0.25-4); Preferably, the cathode catalyst loading in the cathode catalyst layer is 0.5-4 mg / cm³. 2 .
6. The fuel cell membrane electrode assembly according to any one of claims 1-5, wherein, The method for preparing the hydrophobically modified carbon particles includes: The carbon particles are brought into contact with a hydrophobic modifier and then calcined. Preferably, the hydrophobic modifier is selected from at least one of polytetrafluoroethylene, silane-modified materials, fluorocarbon resin, polymethyl methacrylate, and polypropylene; Preferably, the mass ratio of the hydrophobic modifier to the carbon particles is 1:(3-10); Preferably, the roasting temperature is 250-350℃ and the time is 20-60 minutes.
7. The fuel cell membrane electrode assembly according to any one of claims 1-6, wherein, The anode catalyst layer and the cathode catalyst layer each independently contain an ion polymer, which is selected from perfluorosulfonic acid polymers; Preferably, in the membrane electrode, an anodic diffusion layer is provided on the surface of the anode catalyst layer and a cathode diffusion layer is provided on the surface of the cathode catalyst layer along the proton exchange membrane outward; Preferably, the anode diffusion layer and the cathode diffusion layer are each independently selected from carbon paper and / or a microporous layer; Preferably, the anode catalyst and the cathode catalyst are each independently selected from Pt / C catalyst and / or Pt / X catalyst, wherein X is selected from at least one of Co, Ni, Mo, Pd and Au; Preferably, the proton exchange membrane is a perfluorosulfonic acid polymer membrane.
8. A method for preparing a fuel cell membrane electrode according to any one of claims 1-7, comprising: (1) Prepare an anode catalyst layer slurry containing an anode catalyst, hydrophilically modified carbon particles, a dispersant and a solvent; prepare a cathode catalyst layer slurry containing a cathode catalyst, hydrophobically modified carbon particles, a dispersant and a solvent; (2) Under heating conditions, the anode catalyst layer slurry is sprayed onto the surface of one side of the proton exchange membrane, and the cathode catalyst layer slurry is sprayed onto the surface of the other side of the proton exchange membrane.
9. The preparation method according to claim 8, wherein, In the anodic catalyst slurry, the mass ratio of the anodic catalyst, solvent, and dispersant is 1:(20-100):(100-800); Preferably, the mass ratio of the anode catalyst to the hydrophilically modified carbon particles is 1:(0.01-10), more preferably 1:(0.1-4); Preferably, in the cathode catalyst slurry, the mass ratio of cathode catalyst, solvent, and dispersant is 1:(20-100):(100-800); Preferably, the mass ratio of the cathode catalyst to the hydrophobically modified carbon particles is 1:(0.1-10), more preferably 1:(0.25-4).
10. The preparation method according to claim 8 or 9, wherein, The anode catalyst layer slurry and the cathode catalyst layer slurry each independently include an ionomer; Preferably, the mass ratio of the anode catalyst or cathode catalyst to the ionomer is (0.1-10):
1.
11. The preparation method according to any one of claims 8-10, wherein, The preparation method further includes: covering the surface of the anode catalyst layer with an anode diffusion layer, covering the surface of the cathode catalyst layer with a cathode diffusion layer, and then hot pressing; Preferably, the hot pressing conditions include: a temperature of 120-140℃ and a pressure of 2-8 kg / cm². 2 The pressure holding time is 100-200 seconds.
12. A proton exchange membrane fuel cell, characterized in that, Includes the fuel cell membrane electrode according to any one of claims 1-7.
Citation Information
Patent Citations
Direct-methanol fuel cell nano-porous structural film electrode construction method based on sacrificial template method
CN103531826A
Membrane electrode capable of reducing water penetration, and preparation and application thereof
CN109921028A